Varied Presentations and Comorbidities in Pediatric Autoimmune Pancreatitis. Issue 1 (9th February 2021) - Suter, Blair; Patel, Feenalie; Holland, Kathleen; Brown, Brandon P.; Bhatt, Heli; Puri, Kanika; McFerron, Brian; Vanderpool, Charles
Abstract : Autoimmune pancreatitis (AIP) is a chronic inflammatory condition rarely reported in children. In 2018, to standardize the approach to AIP, INternational Study Group of Pediatric Pancreatitis: In search for a cuRE (INSPPIRE) defined AIP, outlined the clinical course, and developed diagnostic and therapeutic recommendations. We performed a retrospective review of cases at our institution from January 1, 2016, to June 1, 2019, and compared their presentations with the INSPPIRE guidelines. Our patients showed variable laboratory, radiographic, and histologic findings, highlighting the difficulty in diagnosing AIP. Histologic samples were obtained in our patients due to diagnostic uncertainty, which ultimately confirmed the diagnosis. One patient was diagnosed with autoimmune hepatitis coexistent with AIP, which has not been previously described in the pediatric population. Exocrine and endocrine complications of AIP were also noted. In all cases, symptoms improved following treatment, and decompression of the common bile duct was seen on repeat imaging.